A Pragmatic Analysis Of Interrogative Utterances In Captain America Movie Manuscript - Purnamasari, Novia; , Dra. Siti Zuhriah Ar., M.Hum; , Drs. Sigit Haryanto, M.Hum (2013)
This research deals with interrogative utterances in Captain America movie. The research aims at describing the types of interrogative utterance, implicature, and violation of Grice Maxims of Captain America movie. The research employs the descriptive qualitative as the type of the research, the data source of this research is the script of Captain America movie. Techniques of collecting data are watching the movie, observing the script of the Captain America movie, signing the interrogative utterances in script of Captain America movie, collecting the data of interrogative utterances and other elements relating with interrogative utterances. The techniques of analyzing data are describing the type of interrogative utterances, describing the implicature of interrogative utterances, describing the maxim violation. The result of the study shows that 1) the types of interrogative are: yes-no question, tag question and, interrogative sentence with word question. 2) The implicature of interrogative utterances covers conventional implicature 12,82% and conversational implicature 87,18%. 3) The maxim often violated by the character is maxim of Quality 10, 26%, Quantity 41, 02%, relevant 2, 57%and manner 33, 33%.